Farmers’ Coping Mechanisms for Common Bean Production under Water-Logged Soil Conditions in Uganda-Rwanda Boarder Region - Athanase, Cyamweshi Rusanganwa; Tenywa, John Steven; Makooma, Moses Tenywa; Okiror, John James; Leonidas, Dusengemungu; Mupenzi, Mutimura; Augustine, Musoni (My University, 2013)
Common bean (Phaseolus vulgaris L.) is a staple food and income crop in eastern Africa, especially within the Uganda-Rwanda boarder region where it constitutes a major component of food security. Unfortunately, bush beans are severely affected by frequent water-logging which persists over a considerable period of the year. In spite of this, farmers have continued to cultivate bush bean though with miserable yields. The study aimed to identify farmers’ indigenous coping mechanisms to the climatic predicament, as a foundation for nurturing and subsequently designing appropriate management strategies for improved bean production in the region. A household survey was conducted in Kisoro district, in a location representative of the ecological conditions of Uganda-Rwanda region. 96 respondents were selected randomly at village level from a list of 500 households provided by the extension workers. Data were collected using semi-structured interviews. Findings showed that farmers possess vital coping mechanisms including construction of ridges, fertiliser application and chemical control of pests and diseases to expedite plant growth, and construction of drainage channels. It is clear that farmers’ indigenous coping mechanisms need further nurturing and refining to improve their performance in dealing with water-logging crisis in the region
Keywords: Ridges, manure, drainage channels, bush bean.